A Case of a Giant Borderline Phyllodes Tumor Early in Pregnancy Treated with Mastectomy and Immediate Breast Reconstruction. Issue 6 (26th August 2016) - Gentile, Lori F.; Gaillard, William Foster; Wallace, Jodi‐Ann; Spiguel, Lisa R. P.; Alizadeh, Layla; Lentz, Ashley; Shaw, Christiana
Abstract: Breast tumors in pregnancy are often times diagnosed at advanced stages secondary to difficulty distinguishing between pathologic from normal physiologic changes. Often benign, phyllodes tumors are rare fibroepithelial stromal tumors of the breast, most commonly diagnosed in the 4th and 5th decades of life. However, these tumors may be characterized by malignancy with metastases in 10% of cases. In this paper, we report a novel case of a young woman presenting at 8 weeks gestation with a large borderline phyllodes tumor. An exceedingly rare condition, with only nine previously reported cases, phyllodes tumors in pregnancy frequently display more aggressive characteristics with larger median tumor size, more malignant potential, and more rapid growth rate. Here, we describe our experience safely and effectively treating this rare condition in a young gravid women with mastectomy and immediate breast reconstruction in the second trimester.